Physical properties of 8OS5 thioester studied by complementary methods. (3rd August 2017) - Deptuch, Aleksandra; Jaworska-Gołąb, Teresa; Marzec, Monika; Fitas, Jakub; Nagao, Keigo; Chruściel, Janusz; Ossowska-Chruściel, Mirosława D.
ABSTRACT: Properties of 4-n-pentylphenyl-4'-n-octyloxythiobenzoate (8OS5), belonging to the nOS5 homologous series, have been studied by complementary methods. The phase sequence, the phase transition temperatures, the thickness of molecular layers, the average distance between long axes of molecules and the correlation length were determined during cooling and heating. For the first time, simultaneous X-ray diffraction and differential scanning calorimetry measurements have been used to study mesomorphic properties. The results are compared with the ones obtained in standard measurements by means of differential scanning calorimetry, X-ray diffraction and polarizing optical microscopy. Meaning of experimental procedures applied in investigations of monotropic mesophases below a melting point is discussed.